The Difference in Perceptual Anticipation Between Professional Tennis Athletes and Second-Grade Athletes Before Batting - Shangguan, Rong; Che, Yuanyuan (Frontiers in Psychology, 2018)
To investigate the differences in cognitive processing of perceptual anticipation of tennis players at different levels before batting by ERPs, we used the skilled - expert paradigm to compare the cognitive and neural mechanism of tennis professional athletes and second – grade athletes when they made perceptual anticipation of the batting line at different time points (the landed time point of ball T0, the time point before 80ms of batting). The performance results showed that, regardless of the T0 or T1 time point, tennis professional athletes had shorter anticipation time and high correct rate on batting line than second-grade athletes; ERP results demonstrated that compared with second-grade athletes, tennis professional athletes induced smaller N1 amplitudes and larger P2 amplitudes in the early perceptual anticipation, and induced smaller N2 and larger P3 amplitudes in the late perceptual anticipation. The tracing analysis results of dipole location found that the N2 component of tennis professional athletes at the T1 time point significantly activated the superior parietal lobule and middle temporal gyrus, while the N2 component of second-grade athletes at T1 time point significantly activated the culmen and middle frontal gyrus. These studies suggest, no matter at early or late stage, tennis professional athletes are faster and more accurate than second-grade athletes on the perceptual anticipation of tennis lines, which possibly since the relevant neural network of former is faster and easier to be activated. The prefrontal cortex may be a critical area of perceptual anticipation in tennis.